INFLUENCE OF SCREW DRIVE FIT CLEARANCE ON SELF-LOCKING ABILITY UNDER VIBRATING INSPIRATION - DU YiMin; LI ZhiHui; JIA XueZhi; LI Ji; KE ShanLiang (Jixie qiangdu)
Screw drive is widely used in the focusing mechanisms in space cameras, and the self-locking ability is required to resist the shock and vibration in the process of launching. The paper establishes a non-linear simplified mechanical model of thread fit clearance with two degrees of freedom. The dynamic response of the system under the vibrating inspiration is achieved by numerical simulation method. The result shows that non-dimensional kurtosis indexes can be used as an indicator to evaluate the degree of self-locking failure of screw drive. Finally, The simplified model is verified by finite element simulation analysis, and it shows kurtosis indexes is effective to analyze the influence of thread fit clearance on self-locking ability.